1996
DOI: 10.1016/0014-5793(96)00168-8
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of peptides homologous to a loop region in human lactoferrin

Abstract: Human lactoferrin contains a 46 residue sequence named lactoferricin H thought to be responsible for its antimicrobial properties. Synthetic peptides HLTI, correspomling to the loop region of human lactoferricin (FQWQR-NMRKVRGPPVS) and HLT2, corresponding to its charged portion (FQWQRNMRKVR), exerted significant antibacterial effects against £. co//serotype O111 strains NCTC 8007 and ML35. The corresponding sequences In native human lactoferrin were shown to adopt a charged helix and hydrophoble tall within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 30 publications
1
68
0
Order By: Relevance
“…The smaller dLPA molecule may be able to more readily gain access to the binding site, whereas the larger LPS molecule would be unable to interact with the site. Binding of LPS (or dLPA) to many LPS-binding proteins is via interaction of the phosphate groups on the LPA with specific positively charged residues within the LPS-binding protein (1,3,14,17,20,21,25,26,28,31,35,39,41). C1INH has one Arg (at position 18) and 3 Lys residues (at positions 22, 30, and 55) within the amino-terminal domain.…”
Section: Discussionmentioning
confidence: 99%
“…The smaller dLPA molecule may be able to more readily gain access to the binding site, whereas the larger LPS molecule would be unable to interact with the site. Binding of LPS (or dLPA) to many LPS-binding proteins is via interaction of the phosphate groups on the LPA with specific positively charged residues within the LPS-binding protein (1,3,14,17,20,21,25,26,28,31,35,39,41). C1INH has one Arg (at position 18) and 3 Lys residues (at positions 22, 30, and 55) within the amino-terminal domain.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, dose-response studies revealed that hLF(1-11) was considerably (P Ͻ 0.05) more efficient than hLF (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) in increasing the membrane permeability of bacteria (Fig. 2).…”
Section: Fig 2 Killing Of Antibiotic-resistant S Aureus (A) L Momentioning
confidence: 95%
“…was applied instead of hLF or hLF Ϫ3N . Synthetic peptides corresponding to residues 1 to 11 of hLF (GRRRRSVQWCA, 1,494 Da), referred to below as hLF (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), and fragments thereof and a peptide corresponding to residues 21 to 31 of hLF (FQWQRN MRKVR, 1,567 Da), referred to below as hLF (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), were prepared and purified as described previously (4). The purity of the synthetic peptides usually exceeded 88%, as determined by reverse-phase high-performance liquid chromatography.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations